Patterns, mechanism of injury and outcome of pediatric trauma at a level 1 trauma centre: a descriptive retrospective analysis - Alansari, Amani N.; Mekkodathil, Ahammed; Peralta, Ruben; Baykuziyev, Temur; Alhussaini, Nour W. Z.; Asim, Mohammad; El-Menyar, Ayman (Frontiers in Pediatrics, 2023)
Background: There is a gap in knowledge on the epidemiology of pediatric trauma in the developing countries. We aimed to describe the injury pattern, mechanism of injury (MOI), and outcomes of pediatric trauma in a level 1 trauma centre in one of the Arab Middle Eastern countries. Methods: A retrospective analysis of paediatric injury data was conducted. All trauma patients (<18y) requiring hospitalization between 2012-2021 were included. Patients were categorized and compared based on the MOI, age-group and injury severity. Results: A 3058 pediatric patients (20% of the total trauma admissions) were included in the study. The incidence rate in 2020 was 86 cases per 100,000 pediatric population in Qatar. The majority were male (78%) and the mean age was 9.3±5.7 yrs. Nearly 40% had head injuries. The in-hospital mortality rate was 3.8%. The median ISS (interquartile range; IQR) was 9 (4-14) and GCS was 15 (IQR15-15). Almost 18% required Intensive Care admission. Road Traffic Injuries (RTI) were more frequent in 15-18y whereas ≤ 4y group was mostly injured by falling objects. The case fatality rate was higher among females (5.0%), and in 15-18y (4.6%) and < 4y (4.4%) group. Pedestrian injuries were more lethal among the MOI. One fifth had severe injury with a mean age of 11±6 and 9.5% had ISS of ≥25. Predictors of severe injury were age (10 years old and above) and RTI. Conclusion: Almost one-fifth of the trauma admissions at the level 1 trauma centre in Qatar is due to traumatic injuries among the pediatric population. Developing strategies that are based on understanding the age- and mechanism-specific patterns of traumatic injuries among the pediatric population remains crucial.